Estudo e implementação de um inversor multinível monofásico controlado por FPGA para aplicações de ensino e pesquisa - Coelho, Carolina Antunes (2016)
In this work is shown a study about the main topologies of multilevel voltage inverters and of different PWM (Pulse Width Modulation) modulation strategies for developing a cascaded H-bridge (CHB) multilevel inverter with up to five voltage levels, controlled by reconfigurable logic device FPGA (Field Programmable Gate Array). The inverter model was implemented and simulated in the Matlab Simulink to synthesize a multilevel waveform with output frequency of 60 Hz from the 2.4 kHz switching frequency. The code of the FPGA was written using the software Quartus II for the amplitude modulations rates: 0.99, 0.8, 0.6, 0.4, and 0.2, and they were all validated with the Altera ModelSim simulator. The DE0 Nano-development kit with FPGA Altera Cyclone IV was used to verify the digital PWM control signals applied to the prototype power board with eight MOSFETs. The simulated and experimental results of the PWM signals to the different levels of amplitude modulation, loads and output filters, with analysis of total harmonic distortion (THD), are presented and corroborates that this study adds to the academic environment one simple, compact and didactic methodology for study and research multilevel inverters with power up to 350 W.